ARTERIAL HYPERTENSION IN THE PRESENCE OF OVERWEIGHT AND OBESITY. THE CAPABILITIES OF AMLODIPINE AND LISINOPRIL COMBINATION. PART 1. FEATURES OF THE DAILY PROFILE OF BLOOD PRESSURE AND HEART DAMAGE AS A TARGET ORGAN IN PATIENTS WITH ARTERIAL HYPERTENSION IN COMBINATION WITH OVERWEIGHT AND OBESITY - O. D. Ostroumova; A. I. Kochetkov; I. I. Kopchjonov; V. M. Fomina (Рациональная фармакотерапия в кардиологии)
The main mechanisms by which obesity and overweight exacerbate heart  damage as a target-organ of arterial hypertension (HT), and also increase the risk of cardiovascular complications are discussed. Features  of the daily profile of blood pressure and features of the pathogenesis of HT in obesity are considered. The description of morphofunctional changes of the heart in patients with HT and obesity, in particular the development of left ventricular hypertrophy, is presented separately. Metabolic factors of cardiac remodeling in obesity (peculiarities of adipogenesis, correlation with the volume of epicardial adipose tissue, the role of adiponectin and leptin) are also described. In describing the disorders of elastic properties of the myocardium in obesity and HT, the authors focus on the changes in the global longitudinal systolic and circumferential strains in this category of patients.